Knowledge and its associated factors on myocardial infarction among the patients attending cardiology clinic, Teaching Hospital, Jaffna - Vathanarani, A.; Vithya, N.; Jegapragash, V; Lakshman, P. (University of Jaffna, 2024)
Myocardial infarction is one of the potentially fatal coronary-associated disorder marked by unexpected cardiac cell death. Globally, it is one of the main causes of death. Patients' knowledge is essential for managing post-MI condition. To enhance the health outcome, patient education and support is most important. The aim of the study is to assess the knowledge on myocardial infarction and associated factors on it among the patients with myocardial infarction attending the cardiology clinic, Teaching Hospital Jaffna. Hospital based descriptive cross-sectional study was conducted among 403 patients with myocardial infarction, attending cardiology clinic, Teaching Hospital Jaffna. A pretested interviewer-administered questionnaire was used to collect the data and systematic random sampling technique was used to select the participants. Ethical clearance was obtained from Ethics Review Committee, Faculty of Medicine, University of Jaffna. The data were entered by using IBM SPSS Statistics 27. The variables were described by using descriptive statistic and the Chi-squared test was used to find the association. Among 403 participants the mean age was 65.18 (SD=±9.811) with the range from 31 to 85 years. Most of them were male (69.5%) and Sri Lankan Tamil (96.5%). Nearly half of them having primary education (51.9%) and 18.6% were not having any formal education. The mean overall knowledge score was 21.33 (SD=±5.282) and two third of participants (68.0%) had adequate knowledge. Knowledge had statistically significant association with level of education (p=<0.001), ethnicity (p=0.040) and monthly family income (p=0.012). There is no any significant association with knowledge and age, gender, religion, marital status, occupation and family history of MI. However, the majority of patients have adequate knowledge on their condition, a significant proportion still lacks on essential understanding on radiating pain as physical symptom and impact of diabetes, physical inactivity, obesity, and high blood pressure as risk factors. To enhance patient knowledge, frequent educational programs will be useful to improve the health outcome.
Keywords: Knowledge; Myocardial infarction; Patient; Associated factors